How is hip anatomy reconstruction and inlay wear associated up to 10 years after primary THA using ceramic on highly crosslinked polyethylene bearings? - Johannes Weishorn; Samira Heid; Thomas Bruckner; Christian Merle; Tobias Renkawitz; Moritz M. Innmann (BMC Musculoskeletal Disorders, 2023)
Abstract Introduction Conventional polyethylene (PE) wear has been reported to be associated with femoral offset reconstruction and cup orientation after THA. Thus, the present study aimed (1) to determine the polyethylene wear rate of 32 mm ceramic heads with highly cross-linked polyethylene (HXLPE) inlays up to 10 years postoperatively and (2) to identify patient and surgery-related factors affecting the wear rate. Methods A prospective cohort study was performed, investigating 101 patients with 101 cementless THAs and ceramic (32 mm) on HXLPE bearings after 6–24 months, 2–5 years and 5–10 years postoperatively. The linear wear rate was determined using a validated software (PolyWare®, Rev 8, Draftware Inc, North Webster, IN, USA) by two reviewers, blinded to each other. A linear regression model was used to identify patient and surgery-related factors on HXLPE -wear. Results After an initial bedding-in phase of 1 year after surgery, the mean linear wear rate was 0.059 ± 0.031 mm/y at ten years (mean 7.7 years; SD 0.6 years, range 6–10), being below the osteolysis relevant threshold of 0.1 mm/year. The regression analysis demonstrated that age at surgery, BMI, cup inclination or anteversion and the UCLA score were not associated with the linear HXLPE-wear rate. Only increased femoral offset showed a significant correlation with an increased HXLPE-wear rate (correlation coefficient of 0.303; p = 0.003) with a moderate clinical effect size (Cohen’s f²=0.11). Conclusion In contrast to conventional PE inlays, hip arthroplasty surgeons may be less concerned about osteolysis-related wear of the HXLPE if the femoral offset is slightly increased. This allows focusing on joint anatomy reconstruction, hip stability and leg length.